Income and education of the states of the United States: 1840–2000 - Scott Baier; Sean Mulholland; Chad Turner; Robert Tamura (Federal Reserve Bank of Atlanta, 2004)
This article introduces original annual average years of schooling measures for each state from 1840 to 2000. The paper also combines original data on real state per-worker output with existing data to provide a more comprehensive series of real state output per worker from 1840 to 2000. These data show that the New England, Middle Atlantic, Pacific, East North Central, and West North Central regions have been educational leaders during the entire time period. In contrast, the South Atlantic, East South Central, and West South Central regions have been educational laggards. The Mountain region behaves differently than either of the aforementioned groups. Using their estimates of average years of schooling and average years of experience in the labor force, the authors estimate aggregate Mincerian earnings regressions. Their estimates indicate that a year of schooling increased output by between 8 percent and 12 percent, with a point estimate close to 10 percent. These estimates are in line with the body of evidence from the labor literature.
Keywords: 330; Bildung; Bildungsertrag; Humankapital; Teilstaat; USA